(untitled) (Research, Society and Development, 2021)
In local/regional development, economic growth is highlighted, but it is important to emphasize social, environmental, cultural and political factors that are fundamental for development, contributing to the promotion of quality of life. Given the above, the objective of the work was to understand the perceptions of local actors of transformation regarding regional development and entrepreneurship in União da Vitória-PR and Porto União-SC. The research was characterized as descriptive and with a qualitative approach. The actors were selected seeking to include representatives of organizations considered to promote the development of both cities: mayors, chamber of shopkeepers, four local universities and even 20 companies. The questionnaire was applied in person at the organizations. The development problems that can interfere in organizations were identified: low income, low consumption potential, lack of qualified labor, limited industrial activity and the fact that they are two cities close together, but located in different states. The actors understood entrepreneurship as the opening of new companies, they recognized that its process is an important factor in the movement of the local economy and in the generation of employment and income. Still, the actors did not see articulation between the two cities in future actions aimed at local development and expressed concerns about the region’s scenario as they did not see prospects for local change. It was possible with the research to better understand how entrepreneurship and local development is seen from the perspective of local actors of transformation.